Unmeasured anions as predictors of mortality in medical intensive care unit - Rafacho, Bruna Paola Murino [UNESP]; Minicucci, Marcos Ferreira [UNESP]; Azevedo, Paula Schmidt [UNESP]; Garcia, Pollyane Cristini [UNESP]; Schnitz, Kurt [UNESP]; Polegato, Bertha [UNESP]; Okoshi, Marina Politi [UNESP]; Tanni, Suzanan Erico [UNESP]; Matsubara, Luiz Shiguero [UNESP]; Zornoff, Leonardo Antonio Mamede [UNESP]; Paiva, Sergio Alberto Rupp de [UNESP] (My University, 2014)
Background and objetive: The present study aimed to evaluate the utility of variables that represent unmeasured anions (anion gap, anion gap corrected for albumin, anion gap corrected for albumin and lactate, base excess and modified base excess) to predict mortality in medical intensive care unit patients. Methods: This prospective study included 156 consecutive patients admitted to a medical intensive care unit in a Medical school hospital between August 2006 and June 2007. Serum levels of potassium, sodium, chloride, C-reactive protein, albumin, and lactate were measured. Variables that represent unmeasured anions and APACHE II score were calculated. Results: Among the studied patients, 60.9% were male, and mean age was 59.2±17.2 years. Mortality rate was 31.4%. Spearman’s test showed correlation among unmeasured anions and lactate. Comparison between survivors and non-survivors showed differences in length of intensive care unit stay, APACHE II score, albumin, C-reactive protein, lactate, anion gap corrected for albumin, base excess, and modified base excess. Anion gap corrected for albumin, base excess, and modified base excess are predictors of medical intensive care unit mortality; however, theirs areas under the ROC curves are smaller than APACHE II score and C-reactive protein. Conclusion: Variables that estimate unmeasured anions, such as anion gap corrected for albumin, base excess, and modified base excess, can be used to predict mortality in medical intensive care unit patients.

Justificativa e objetivo: O presente estudo teve como objetivo avaliar a utilidade de variáveis que representam ânions não mensuráveis (ânion gap, ânion gap corrigido para a al - bumina, ânion gap corrigido para a albumina e lactato, excesso de base e excesso de base modificado) para prever a mortalidade em pacientes de unidade de terapia intensiva. Métodos: Foram incluídos 156 pacientes consecutivos admitidos na unidade de terapia intensiva em um hospital escola de Medicina entre agosto de 2006 e junho de 2007. Os níveis séricos de potássio, sódio, cloreto, proteina C-reativa, albumina e lactato foram medidos. Foram calculadas variáveis que representaram os ânions não mensuráveis e APACHE II. Resultados: Entre os pacientes estudados, 60,9% eram do sexo masculino, e a idade média foi de 59,2±17,2 anos. A taxa de mortalidade foi de 31,4%. O teste de Spearman mostrou correlação entre ânions não mensuráveis e lactato. A comparação entre sobreviventes e não sobreviventes mostrou diferenças no tempo de permanência na unidade de terapia intensiva, APACHE II, albumina, proteína C-reativa, lactato, ânion gap corrigido para a albumina, excesso de base e excesso de base modificado. Ânion gap corrigido para a albumina, excesso de base e excesso de base modificado foram preditores de mortalidade na unidade de terapia intensiva médica, mas as áreas sob as curvas ROC foram menores do que o escore APACHE II e a proteína C-reativa. Conclusão: Variáveis que estimam ânions não mensuráveis, como o ânion gap corrigido para a albumina, o excesso de base e o excesso de base modificado, podem ser usados para prever a mortalidade em pacientes em unidade de terapia intensiva clínica.
Ânions não mensuráveis podem predizer mortalidade em unidade de terapia intensiva clínica
Keywords: Acidosis; Acid-base equilibrium; C-reactive protein; APACHE; Critical care; Intensive care units; Mortality; Acidose; Equilíbrio ácido-base; Proteína C-reativa; APACHE; Cuidados críticos; Unidades de terapia intensiva; Mortalidade